Chinese species of Nomia (Gnathonomia) Pauly, 2005 (Hymenoptera: Apoidea: Halictidae: Nomiinae) - Zhang, Dan; Niu, Ze-Qing; Orr, Michael C.; Ascher, John S.; Zhu, Chao-Dong (Zootaxa, 2020)
Five Chinese species of Nomia (Gnathonomia) Pauly, 2005 are treated in this paper: Nomia fusciventris Zhang & Niu, sp. nov. from Fujian Province is described as a new species; N. aurata Bingham, 1897 and N. wahisi Pauly, 2009 are recorded from China for the first time, and the male of N. pieli Cockerell, 1931 is newly reported. An updated diagnosis is provided for the subgenus Nomia (Gnathonomia) to accommodate Chinese endemic species which lack the white integumental bands found in most previously described forms. A key to the known Chinese species is provided.